The impact of organizational development on the competitive advantage of Ma'an Development Company and Aqaba Development in Jordan - Salah, Ali Atta; Al Atili, Manal Abdul Rahman; Al Farajat, Jihad Mousa (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed at revealing the impact of organizational development on the competitive advantage of Ma'an Development Company and Aqaba Development in Jordan. The study sample consisted of (55) male employees and (45) female employees in both companies. There is an impact of competitive advantage in all six axes on organizational development, which is of great importance to both companies. The organizational average of Ma'an Development Company (1.825) was higher than that of Aqaba Development Company (1.801), the rest of the arithmetical averages of the study axes were high and were in favor of ADC, which means that they are of great importance to the company. And there are statistically significant differences in the level of the organizational advantage indicating the organizational development of the two companies and in favor of ADC. There are also statistically significant differences in the polarization of human resources on organizational development, the impact of the cost on organizational development, and the impact of innovation on organizational development, all of which came in favor of ADC.
Keywords: organizational development; competitive advantage